Sejong's Effects on People's Health: Consequences of a Long Commute - Seulgi Lim; Soohyung Lee (Institute of Labor Economics (IZA), 2023)
We examine the health impacts of long commute time by exploiting a large-scale placed-based policy in South Korea. The policy relocated public employers in the capital area to disadvantaged cities. However, some public employees kept their residences in the capital area and spend long hours commuting. Using this change, we estimate 2SLS models whose results suggest that having a long commute substantially increases usage of medical services, particularly to treat respiratory, circulatory, and endocrine & metabolic diseases. However, we find mixed effects of long commute time on medical checkup outcomes and health-related activities such as exercise.
Keywords: I10; J18; H51; R11; 330; commute; health; place-based policy; Sejong; innovation city